Potentiometric Study of the Complexation of Silver Ions with Some Crown Ethers in Binary Acetonitrile-Water Solutions - Semnani, Abolfazl; Reza Pouretedal, Hamid; Reza Firooz, Ali; Morteza Talebi, Sayed (Asian Journal of Chemistry, 2010)
A potentiometric study concerning the interaction between silver ion and several crown ethers in different acetonitrile-water mixtures has been carried out at 25°C. The formation constants of the resulting 1 : 1 complexes were determined from the potentiometric data and found to vary in the order: C222 > DA18C6 > A18C6 > 18C6 > 15C5 > DB 18C6 > DB3OClO > B15C5 > 12C4 > DB24C8. The stability constants of complexes increased with increasing the water content of the solvent mixtures until 20% (w/w). However, in further water percentages, the formation constants will reduce. The possible reason for such observation has been discussed in terms of the topology of the ligands and the specific interactions of the acetonotrile with the ligands and silver ion.